Increasing the clinical efficacy of NK and antibody-mediated cancer immunotherapy: potential predictors of successful clinical outcome observed in high-risk neuroblastoma - Tony A. Koehn; Lori L. Scardino; Kory L. Alderson; Amy K. Erbe; Kim A. McDowell; Bartosz eGrzywacz; Jacquelyn A. Hank; Paul Mark Sondel (Frontiers Media S.A., 2012)
Disease recurrence is frequent in high-risk neuroblastoma (NBL) patients even after multimodality aggressive treatment [a combination of chemotherapy, surgical resection, local radiation therapy, autologous stem cell transplantation (ASCT) and cis-retinoic acid (CRA)]. Recent clinical studies have explored the use of monoclonal antibodies (mAbs) that bind to disialoganglioside (GD2), highly expressed in NBL, as a means to enable immune effector cells to destroy NBL cells via antibody-dependent cell-mediated cytotoxicity (ADCC). Preclinical data indicate that ADCC can be more effective when appropriate effector cells are activated by cytokines. Clinical studies have pursued this by administering anti-GD2 mAb in combination with ADCC-enhancing cytokines (IL2 and GM-CSF), a regimen that has demonstrated improved cancer-free survival. More recently, early clinical studies have used a fusion protein that consists of the anti-GD2 mAb directly linked to IL2, and antitumor responses were seen in the Phase II setting. Analyses of genes that code for receptors that influence ADCC activity and Natural Killer (NK) cell function [Fc Receptor (FcR), Killer Immunoglublin-like Receptor (KIR), and KIR-ligand (KIR-L)] suggest patients with antitumor activity are more likely to have certain genotype profiles. Further analyses will need to be conducted to determine whether these genotypes can be used as predictive markers for favorable therapeutic outcome, thus potentially increasing the efficacy of mAb-mediated NK cell-based cancer immunotherapy.